2018
DOI: 10.1093/bioinformatics/bty766
|View full text |Cite
|
Sign up to set email alerts
|

PhysiBoSS: a multi-scale agent-based modelling framework integrating physical dimension and cell signalling

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

5
5

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 77 publications
(113 reference statements)
3
139
0
Order By: Relevance
“…Contacts between agents were modeled as a hard-core repulsive force, F r , effective as soon as spheres overlapped (Ghaffarizadeh et al, 2018; Letort et al, 2019):trueFr=cr)(1trueddeqtruedtrued,where trued is the vector between the two sphere centers and d eq is the equilibrium distance (i.e., the sum of the two sphere radii). Thus, when two spheres came into physical contact, the increasing overlap, which generated an increasing deformation of the spheres, created a repulsive force (Drasdo et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Contacts between agents were modeled as a hard-core repulsive force, F r , effective as soon as spheres overlapped (Ghaffarizadeh et al, 2018; Letort et al, 2019):trueFr=cr)(1trueddeqtruedtrued,where trued is the vector between the two sphere centers and d eq is the equilibrium distance (i.e., the sum of the two sphere radii). Thus, when two spheres came into physical contact, the increasing overlap, which generated an increasing deformation of the spheres, created a repulsive force (Drasdo et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Its modular design allows further customization by open source contributors. For example, Letort et al recently integrated Boolean signalling networks into each cell agent to model molecular-scale processes 31 .…”
Section: Physicell: a Platform For Multicellular Systems Biologymentioning
confidence: 99%
“…Some modeling approaches have tackled this issue using an agent-based formalism: each agent corresponds to a cell, whose activity depends on that of its neighbors [9,10] (i.e., CellSys [11], PhysiCell [12] ). Attempts to explicitly include regulatory networks into these agents [13] have shown that this can easily become computationally costly or would increase considerably the number of parameters to tune (e.g., PhysiBoSS [14]). Other applications rely on cellular automata, e.g., Epilog [15], or yet on the Potts model, which can be also considered as an agent-based approach [16].…”
Section: Introductionmentioning
confidence: 99%